Crossing thresholds: the lexicalization and performance of memory in early imperial funerary inscriptions from Sicily - Victoria Beatrix Fendel (Lexis: Journal in English Lexicology)
The article explores the diction of the funerary (and honorific) inscriptions from three early imperial (1 BC to AD 401) Sicilian cities, i.e. Catania, Termini, and Syracuse. By means of the I.Sicily Sketch Engine corpus, three sub-samples were drawn reflecting syntactic (asyndesis), pragmatic (Dis Manibus (Sacrum)), and semantic-lexemic (symbols, indexes, icons) phrasemes in the sense of Mel’čuk’s Sens-Texte framework. The article conceptualises cemeteries with Foucault as heterotopic spaces with language / diction as a gatekeeper. The cemetery thus becomes a space for reflection on the differences between (i) individual, social, and cultural memory, (ii) pre-colonial (pagan) past and imperial (Christian) present, and (iii) language and identity choices. This reflection is externalised by means of the symbol system of language. While at the cultural level we see convergence (with customisation), at the social and individual levels flexibility prevails as the diction of the funerary inscriptions reflects. While early imperial Sicily seems to form a cultural space, smaller sub-groups, especially the Christian and polis communities, could express distinctive identity and memory choices. Individual variation focusses on the conceptualisation of the link between deceased and dedicator and the function of the memorial monument and reflects the dedicators’ bilinguality. This kind of variation highlights personal experience of collective remembrance.